PERANCANGAN SISTEM INFORMASI TRANSAKSI PENJUALAN PADA GADIS DESA KOPI - Muhammad Anwar; Furqoni Yudhistira, Ismailah (CV. ADIBA AISHA AMIRA, 2023)
The purpose of research was to analyze the system used in Gadis Desa Kopi, and provide solutions that facilitates the earlier filing process using a manual by logging in a book and would still take considerable time with keeping track and transaction calculations. It can now be easy to compute and transaction calculations because the data can be stored in a database so it can facilitate barista information and transaction calculations at Gadis Desa Kopi. The methodology used to design this transaction information system is by means of data analysis and field observations. Compilers also used interviews and documentation methods to obtain more complete data. System development method uses the waterfall method. The application of the transaction information system will enhance the performance of barista Gadis Desa Kopi